Toxicological evaluation and metabolism of two N-alkyl benzamide umami flavour compounds: N-(heptan-4-yl)benzo[d][1, 3]dioxole-5-carboxamide and (R)-N-(1-methoxy-4-methylpentan-2-yl)-3, 4-dimethylbenzamide. (2016) - Karanewsky, Donald S.; Arthur, Amy J.; Liu, Hanghui; Chi, Bert; Ida, Lily
Abstract: Toxicological evaluations of two N -alkyl benzamide umami flavour compounds, N -(heptan-4-yl)benzo[d][1, 3]dioxole-5-carboxamide (S807, CAS 745047-51-2) and ( R )- N -(1-methoxy-4-methylpentan-2-yl)-3, 4-dimethylbenzamide (S9229, CAS 851669-60-8), were completed for the purpose of assessing their safety for use in food and beverage applications. Both S807 and S9229 undergo rapid oxidative metabolism by both rat and human liver microsomes in vitro . In pharmacokinetic studies in rats, the systemic exposure to S9229 on oral administration is very low at all doses (% F < 1%), while that of S807 demonstrated a non-linear dose dependence. In metabolism studies in rats, hydroxylation of the C-4 aryl methyl group was found to be the dominant metabolic pathway for S9229. The dominant metabolic pathway for S807 in the rat involved oxidative scission of the methylenedioxy moiety to produce the corresponding 3, 4-dihydroxybenamide which is further converted by Phase II metabolic enzymes to the 3- and 4- O -methyl ethers as well as their corresponding glucuronides. Both S807 and S9229 were not found to be mutagenic or clastogenic in vitro, and did not induce micronuclei in polychromatic erythrocytes in vivo . In a subchronic oral toxicity study in rats, the no-observed-effect-level (NOEL) for S807 was 20 mg/kg bw/day when administered in the diet for 13 weeks. The no-observed-adverse-effect-level (NOAEL) for S9229 in rats was 100 mg/kg bw/day (highest dose tested) when administered in the diet for 28 consecutive days.